(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
This article examines the concepts of ens politicon and ens rationale in the context of contemporary ethical-rational decline. Through an analytical-philosophical approach, this research explores how humans, as political beings (ens politicon) and rational beings (ens rationale), face the challenges of moral degradation and the decline of rationality in the modern era. The analysis shows that ethical-rational decline is manifested in various phenomena such as post-truth politics, social polarization, and the crisis of institutional legitimacy. It appears that reconciliation between the political and rational dimensions of humankind is crucial in overcoming this crisis. Therefore, an integrative approach that combines practical wisdom (phronesis) with democratic deliberation can provide a way out of ethical-rational decline. The development of critical capacity is absolutely necessary as a foundation for restoring a rational-ethical ethos in contemporary political life.